2013
DOI: 10.1186/1756-0500-6-347
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis with fulminant type 1 diabetes mellitus diagnosed by cardiovascular magnetic resonance imaging: a case report

Abstract: BackgroundFulminant type 1 diabetes is a non-autoimmune disorder characterized by sudden onset. This complication is rarely associated with myocarditis, suggesting an involvement of viral infection. We report a patient with myocarditis who was admitted for fulminant type 1 diabetes and diagnosed using a combination of non-invasive techniques.Case presentationWe describe the case of a 25-year-old Japanese man with fulminant type 1 diabetes complicated by myocarditis. The patient was admitted with flu-like sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…Figure 4 presents a summary of previously reported cases of simultaneous type 1 diabetes onset and myocarditis. [11][12][13][14] No similar trends in age, sex, HLA-DR, or HLA-DQ were observed. However, all patients exhibited a combination of FT1D and myocarditis within 2 weeks after flu-like symptoms with fever.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 4 presents a summary of previously reported cases of simultaneous type 1 diabetes onset and myocarditis. [11][12][13][14] No similar trends in age, sex, HLA-DR, or HLA-DQ were observed. However, all patients exhibited a combination of FT1D and myocarditis within 2 weeks after flu-like symptoms with fever.…”
Section: Discussionmentioning
confidence: 97%
“…10) Several cases of concurrent type 1 diabetes and myocarditis have been reported. [11][12][13][14] Here, we report a patient with concomitant FT1D and fulminant viral myocarditis related to parainfluenza-3 infection and review reported cases of simultaneous type 1 diabetes and myocarditis.…”
mentioning
confidence: 99%
“…The association between type II diabetes mellitus and viral infections has not been strongly established in the literature. Different viral infections including mumps, measles, echovirus, Epstein-Barr virus (EBV), and coxsackievirus have been traditionally associated with the onset of type I diabetes mellitus [ 4 - 8 ]. In one study, three patients, who developed ketosis-prone diabetes mellitus immediately after documented viral infection with EBV or coxsackievirus and required insulin therapy on discharge, were followed for four to eight years; the first patient remained insulin-dependent throughout the life, the second one regained normal glucose tolerance, and the third one was being transitioned to oral antidiabetic medications [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some cases showing a definite association with acute pancreatitis have been reported [ 3 , 4 ]. Several cases of FT1D also reportedly exhibited myocarditis [ 5 8 ]. To our knowledge, however, no prior reports on FT1D have documented a patient who showed acute pancreatitis and myocarditis within 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiology of FT1D remains elusive. Several cases with concomitant acute pancreatitis [ 3 , 4 ] or myocarditis [ 5 8 ] during the clinical course of FT1D were previously reported. Herein, we describe a 31-year-old Japanese woman with FT1D who was initially diagnosed with acute pancreatitis and then developed diabetic ketoacidosis and myocarditis.…”
Section: Introductionmentioning
confidence: 99%